2017
DOI: 10.5178/lebs.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Parental Condition and Infant Sex at Birth in the Japan Environment and Children’s Study: A Test of the Trivers–Willard Hypothesis

Abstract: The Trivers–Willard hypothesis predicts that females in good condition should bear more sons rather than daughters in certain mammals, including humans. This study tests the hypothesis by using 66,638 childbirth records from a national birth cohort survey in current Japan. Our analyses showed that, contrary to the hypothesis, indicators of parental condition, such as mother’s age, body mass index, job status, education level, medical history, or household income, had few statistically significant effects on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Based on a study on lifetime reproductive success, Leimar (1996) suggested that under certain circumstances, high quality women can have a higher reproductive value than high quality men. Our results are in line with other studies (Douhard 2017;Ellis and Bonin 2002;Keller et al 2001;Kolk and Schnettler 2016;Kozieł and Ulijaszek 2001;Morita et al 2017), which did not find support for the TWH.…”
Section: Discussionsupporting
confidence: 92%
“…Based on a study on lifetime reproductive success, Leimar (1996) suggested that under certain circumstances, high quality women can have a higher reproductive value than high quality men. Our results are in line with other studies (Douhard 2017;Ellis and Bonin 2002;Keller et al 2001;Kolk and Schnettler 2016;Kozieł and Ulijaszek 2001;Morita et al 2017), which did not find support for the TWH.…”
Section: Discussionsupporting
confidence: 92%
“…Several of these findings, though, have been questioned on statistical grounds [33][34][35], and other studies have not supported the hypothesis (including very large birth cohort studies, e.g. [8,36,37]). Our findings are incompatible with the basic effect: if offspring sex ratio was calibrated to heritable traits, then it would necessarily be heritable to some degree as well.…”
Section: Discussionmentioning
confidence: 99%
“…This finding, however, does not universally hold. Offspring numbers have been found to grow with income, wealth and educational level in men in most countries, whereas an inverse pattern, or no pattern at all, is true for women (Fieder & Huber 2007;Hopcroft, 2006Hopcroft, , 2015Nettle & Pollet, 2008;Goodman & Koupil, 2010;Lappegård & Rønsen, 2013;Morita et al, 2017;Nisén et al, 2018). For example Cameron and Dalerum (2009) investigated a group of the wealthiest people in the world (400 people from the Forbes billionaire list) and found that male billionaires had significantly more children, and a more variable number of children, than female billionaires.…”
Section: Introductionmentioning
confidence: 99%